Gratitude and prosociality: a behavioural economics and psychometric perspective - Ma, Lawrence K. (2017)
We feel gratitude—a positive emotion upon receiving an undeserved benefit which is attributable to the givers’ benevolent intent (Watkins, 2007, 2014). Meanwhile, indebtedness symbolises an unpleasant mental state which is also triggered by benefit receipts (Greenberg, 1980). Theories and empirical evidence in the literature have highlighted how gratitude and indebtedness each relates to prosociality (or sanctioning), and importantly, how via different routes these two constructs will elicit cooperativeness. Nonetheless, there is still a gap in the literature on how gratitude and indebtedness will contribute to prosociality and sanctioning in economic exchanges (Leung, 2011). Thus via three economic games (i.e. Experiments 1 to 3, presented in Chapters 2 to 5) I endeavour to thoroughly examine how gratitude (and indebtedness) would relate to prosociality or sanctioning in a Behavioural Economics context. In so doing I intend to combine Psychometrics and Experimental Economics in the examination of the gratitude (and indebtedness)-prosociality association. Additionally, via meta-analysing (i.e. Chapter 2) over three decades of research on the gratitude-prosociality link I intend to offer i) a comprehensive quantitative synthesis of the findings and, ii) a systematic exploration of moderators, which are both absent in the literature. The present thesis also features a series of extensive follow-up analyses on an interesting economic observation from Experiment 1— i.e. the cheap-rider problem (Cornes & Sandler, 1984). While Experiment 2 entails a more focused scrutiny (via a one-shot game) over the occurrences and motives behind cheap-riding, Experiment 3 builds on that by testing how cheap-riding may be used to enforce normative fairness in an iterated exchange context. Results of the meta-analysis revealed a moderate positive link between gratitude and prosociality. The moderator analyses showed that this link is stronger when, a) state rather than trait gratitude was measured, b) direct instead of indirect or non-reciprocal outcomes was examined, and c) benefit-triggered instead of generalized gratitude (Lambert et al., 2009) was examined. Meanwhile, results of Experiment 1 built upon the above by showing how the gratitude-reciprocity link will be subject to helper intent attribution, and how the injunctive fairness norm (Elster, 2006) could influence this attribution and thereby shaped recipients’ feeling of gratitude (or indebtedness) throughout the episode, and ultimately his/her urge to directly reciprocate. Additionally, a noticeable degree of cheap-riding was observed when unfairly treated participants were granted an avenue to sanction their helpers. The data of Experiment 2 revealed a pattern of cheap-riding that corresponded not only to that of Experiment 1 but also to the reality. Crucially, the analyses of the motives behind repayment allowed the disentanglement of the psychology between that of the cheap-riders, cooperators, and free-riders. Lastly, analyses of Experiment 3 revealed three main findings. They included, a) people’s preference for an ‘optimal’ platform for cheap-riding to better serve its norm-enforcing function, although its actual efficacy in promoting mutual compliance to normative fairness is still questionable; b) how the Relative Rank Model of Gratitude (Wood, Brown, & Maltby, 2011) will supersede the injunctive fairness norm in guiding the recipients’ benefit appraisals, experienced gratitude, and eventual direct reciprocal acts toward the helpers; and c) how gratitude and indebtedness were both predictive of more trustworthiness and generosity in an iterated, variant of Trust Game.